Rancang Bangun Aplikasi Urun Dana Berbasis Website Untuk Membeli Dan Membagikan Hasil Panen Petani Kepada Masyarakat Pra-Sejahtera - M. Rikza As-subhy; Junita Junita; Marincan Pardede (FaST - Jurnal Sains dan Teknologi (Journal of Science and Technology), 2026)
The Indonesian agricultural sector faces structural problems such as low selling prices, instability in the income of small-scale farmers, waste of harvests, and food insecurity among underprivileged communities. This study developed Bagipanen, a web- and Android-based crowdfunding application that integrates a socialfunding model with a mechanism for selling harvests on consignment. The system is designed to connect farmers as commodity providers, donors as funding supporters, and underprivileged communities as beneficiaries. Technically, the application is built using Laravel for the web platform and Flutter for the mobile platform, and is integrated with the Midtrans payment gateway. The research methodology focuses on software engineering with the application of testing through 25 test scenarios covering unit, integration, end-to-end (E2E) testing using Laravel Dusk, performance, and security, with a success rate of 100%. E2E testing results showed an average execution time of 5.35 seconds per scenario, while payment integration testing showed a failure rate of 0%, an average response time of 320 ms, and successful handling of idempotent callbacks. Performance testing recorded a throughput of 33.96 requests/second with a maximum response time of 850 ms at peak load. Software quality analysis showed 87.8% test coverage, 2.3% code duplication, and no critical security vulnerabilities were found.